Increased breakdown of kynurenine towards its neurotoxic branch in bipolar disorder - Birner, Armin; Platzer, Martina; Bengesser, Susanne Astrid; Dalkner, Nina; Fellendorf, Frederike T.; Queissner, Robert; Pilz, Rene; Rauch, Philipp; Maget, Alexander; Hamm, Carlo; Herzog-Eberhard, Simone; Mangge, Harald; et al. (PLOS ONE, 2017)
Introduction Bipolar disorder (BD) is a chronic psychiatric disease which can take most different and unpredictable courses. It is accompanied by unspecific brainstructural changes and cognitive decline. The neurobiological underpinnings of these processes are still unclear. Emerging evidence suggests that tryptophan catabolites (TRYCATs), which involve all metabolites of tryptophan towards the kynurenine (KYN) branch, are involved in the etiology as well as in the course of BD. They are proposed to be mediators of immune-inflammation and neurodegeneration. In this study we measured the levels of KYN and its main catabolites consisting of the neurotoxic hydroxykynurenine (3-HK), the more neuroprotective kynurenic acid (KYNA) and anthranilic acid (AA) and evaluated the ratios between end-products and substrates as proxies for the specific enzymatic activity (3-HK/KYN, KYNA/KYN, AA/KYN) as well as 3-HK/KYNA as a proxy for neurotoxic vs. neuroprotective end-product relation in individuals with BD compared to healthy controls (HC). Methods We took peripheral TRYCAT blood levels of 143 euthymic to mild depressive BD patients and 101 HC. For statistical analyses MANCOVA’s controlled for age, sex, body mass index, cardiovascular disease and smoking were performed. Results The levels of KYNA (F = 5,579; p <.05) were reduced in BD compared to HC. The enzymatic activity of the kynurenine-3-monooxygenase (KMO) reflected by the 3-HK/KYN ratio was increased in BD individuals compared to HC (F = 5,394; p <.05). Additionally the ratio of 3-HK/KYNA was increased in individuals with BD compared to healthy controls (F = 11,357; p <.01). Discussion In conclusion our findings subserve the concept of KYN -pathway alterations in the pathophysiology of BD. We present evidence of increased breakdown towards the neurotoxic branch in KYN metabolism even in a euthymic to mild depressive state in BD. From literature we know that depression and mania are accompanied by inflammatory states which should be capable to produce an even greater imbalance due to activation of key enzymes in the neurotoxic direction of KYN -conversion. These processes could finally be involved in the development of unspecific brain structural changes and cognitive deficits which are prevalent in BD. Further research should focus on state dependent changes in TRYCATs and its relation to cognition, brain structure and staging parameters.